PENGARUH POLA ASUH DEMOKRATIS ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Adilah Maulida (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
ABSTRACT Education is considered an important aspect of individuals' lives and the progress of a nation. One of the important subjects in the basic education curriculum is mathematics, which is regarded as a universal science that plays a crucial role in the development of technology and various disciplines. However, students' mastery of mathematics at the elementary school level remains a frequently encountered problem, as indicated by the national examination results showing a low passing percentage. Several factors influence students' ability to comprehend mathematics lessons, including their low ability to receive course materials, learning difficulties faced by students, and challenges encountered by teachers in teaching mathematics. This study also highlights the role of the educational environment, especially the family, in influencing the quality of children's education. Parenting styles applied by parents have a significant impact on their children's education. Parents who implement a democratic parenting style provide opportunities for their children to learn independently and make their own decisions, thereby helping to enhance their cognitive and social abilities. However, many parents still do not understand the importance of a democratic parenting style in shaping their children's character and improving their learning outcomes. This research was conducted at Sudimara Timur 2 Elementary School, with fourth-grade students as the research subjects. The research method used was data collection through observation, interviews, and document analysis. The obtained data were then analyzed to determine the influence of parents' democratic parenting style on students' learning outcomes in mathematics. It is expected that the results of this research will contribute to enriching the literature on democratic parenting styles and provide useful information and recommendations for parents, teachers, and educational institutions in improving the quality of education and students' learning outcomes. ABSTRAK Pendidikan dianggap sebagai hal penting dalam kehidupan individu dan kemajuan suatu bangsa. Salah satu mata pelajaran penting dalam kurikulum pendidikan dasar adalah matematika, yang dianggap sebagai ilmu universal yang memiliki peran penting dalam perkembangan teknologi dan berbagai disiplin ilmu. Namun, penguasaan matematika siswa di tingkat SD masih menjadi permasalahan yang sering dihadapi, terlihat dari hasil ujian nasional yang menunjukkan persentase kelulusan rendah. Beberapa faktor yang mempengaruhi kemampuan siswa dalam memahami pelajaran matematika diantaranya rendahnya kemampuan siswa dalam menerima materi pelajaran, kesulitan belajar yang dihadapi siswa, dan kesulitan yang dihadapi guru dalam mengajarkan matematika. Penelitian ini juga menyoroti peran lingkungan pendidikan, terutama keluarga, dalam mempengaruhi kualitas pendidikan anak. Pola asuh yang diterapkan oleh orang tua memiliki dampak signifikan terhadap pendidikan anak. Orang tua yang menerapkan pola asuh demokratis memberikan kesempatan pada anak untuk belajar mandiri dan mengambil keputusan sendiri, sehingga membantu meningkatkan kemampuan kognitif dan sosial anak. Namun, masih banyak orang tua yang belum memahami pentingnya pola asuh demokratis dalam membentuk karakter dan meningkatkan hasil belajar anak. Penelitian ini dilakukan di SDN Sudimara Timur 2 dengan subjek penelitian siswa kelas IV. Metode penelitian yang digunakan adalah pengumpulan data melalui observasi, wawancara, dan analisis dokumen. Data yang diperoleh kemudian dianalisis untuk menentukan pengaruh pola asuh demokratis orang tua terhadap hasil belajar siswa pada mata pelajaran matematika. Diharapkan hasil penelitian ini dapat memberikan kontribusi dalam memperkaya literatur tentang pola asuh demokratis dan memberikan informasi dan rekomendasi yang berguna bagi orang tua, guru, dan lembaga pendidikan dalam meningkatkan kualitas pendidikan dan hasil belajar siswa.